THE IMPORTANCE OF COMPLIANCE WITH SANITARY AND HYGIENIC REQUIREMENTS IN THE PREPARATION OF FAST FOOD IN FOOD SERVICE ESTABLISHMENTS (World Conference on Social Sciences, Law and Public Policy, 2026)
Currently, the consumption of fast food in public catering establishments, particularly in small food outlets, has been steadily increasing. This trend makes compliance with food safety standards and sanitary-hygienic requirements a priority task. Under the conditions of Uzbekistan, adherence to sanitary and hygienic regulations in public catering enterprises, the scientific basis of hygienic rules in the storage and preparation of food products, and the implementation of these requirements play an important role in protecting consumer health and ensuring food safety.